WATER RESOURCES MANAGEMENT IN UKRAINE - , В. И., А. Л., Е. Ю., А. В., Э. Ю. (Municipal economy of cities. Series: «Economy science», 2013)
The features of the management of water resources of Ukraine on the basis of the introduction of technologies for efficient use of energy-saving projects, analyzes the features of finding new models of management software, investigate the situation conceptual consistency of the management structure of Water Resources of Ukraine on the basis of implementing the components of innovative water management systems in Ukraine.